Efficacy and safety of belimumab for the treatment of refractory childhood-onset systemic lupus erythematosus: A single-center, real-world, retrospective study - Wang, Dahai; Shan, Chunrong; Liu, Jia; Zhang, Ranran; Zhu, Guohao; Gao, Tingting; Chang, Hong; Gao, Shan; Bai, Cui; Nie, Nana; Zhang, Qiuye; Lin, Yi (Frontiers in Immunology, 2022)
Objective: This study aimed to investigate the efficacy and safety of belimumab for treating children with refractory childhood-onset systemic lupus erythematosus (cSLE). Methods: Twenty-six cSLE patients who received belimumab treatment in our hospital from January 2020 to September 2021 (23 of them for more than 52 weeks) were enrolled in this study. Their clinical and laboratory data, assessment of disease activity, glucocorticoid dosage, and treatment-emergent adverse events (TEAEs) were retrieved for analysis. The paired samples t-test and the nonparametric test were used to compare the baseline and post-treatment data. Results: The mean age of onset was 10.3±2.4 years old; the mean disease duration was 41.6±37.4 months; the median Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K) score was 10 (P25, P75: 3, 17); and the mean Physician’s Global Assessment (PGA) score at baseline was 1.9±1.0. Compared with the baseline values, there was a significant decrease in the 24-h urine protein quantifications at 24 and 52 weeks of treatment (P<0.05) as well as elevated complement (C) 3 and C4 levels at 4, 12, 24, and 52 weeks of treatment. In addition, the SLEDAI-2K and PGA scores as well as the percentage of CD19+ B cells were significantly decreased at 12, 24, and 52 weeks of treatment compared with the baseline values (P<0.05). The dosage of glucocorticoid at 4, 12, 24, and 52 weeks of treatment was significantly less than that at baseline or the previous follow-up (P<0.05). At 52 weeks, 14 subjects (53.8%) achieved Lupus Low Disease Activity State (LLDAS), and 4 subjects (15.4%) reached clinical remission (CR). At the last follow-up, 16 subjects (61.5%) achieved LLDAS, and 10 subjects (38.5%) reached CR. Conclusions: Belimumab treatment can significantly improve laboratory indicators, reduce disease activity, and decrease the dosage of glucocorticoid required in children with cSLE. Moreover, it has a good safety profile.